Impact of Electronic Games on the Behavior of Children and their Academic Achievement upon Schools in Mosul City - Radhwan Husain Ibrahim1, Adbul Kareem Ghanim2, Hana A. Alkhaderjameel2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The research aims at finding the effects of electronic games on the behavior of children and finding the relationship between the demographic information and the impact of these games on their behavior and educational achievement. A descriptive and analytical study of the effects of electronic games on the behavior of 60 children in the schools of Mosul city, conducted for the period from Feb.2019 to March 2019. (Non-probability) The sample was chosen according to us of phone or computer and other smart devices for the purpose of playing. Boys and girls equally chosen after fill a questionnaire which was used with a semi-guideline for collecting information. Results of the study revealed that time taken by the students to play a daily or intermittent basis is less than two hours, at 45.7%, and that higher than who spend one to two hours are 32.6% and those who spend more than two hours are 21.6%. Students playing electronically at the age of 3-6 are 19.5%at 7-8 years at 43.5% and, at 9 years are over 37.0%.Yes, No, sometimes are answers of questionnaire.?2 value was less than p<0.05.The study showed differences between males and females in use of games.The study recommends Ministry of Higher Education, with assistance and participation of Ministry of Education, should develop an educational program for parents about electronic games and their harm to children.